Community Acquired Pneumonia Complications in a Tertiary Care Hospitalized Patients - Dr. Abdullah Jan Shinwari; Dr. Kamran Zafarzai; Dr. Yama Sediqi (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2019)
Background: Community-acquired pneumonia (CAP) is a common respiratory infectious disease and major cause of mortality and morbidity in our country. Recent data on the complications rate of the CAP are not readily available in the Eastern region of Afghanistan. Aim: The aims of the study were to identify the rate and type of complications of the CAP in the Internal Medicine Ward of Nangarhar Regional Hospital in the east of Afghanistan. Methods: A prospective analytic study was carried out from (March 2019) to (October 2019) on 120 patients with CAP, who met the inclusion criteria. Data relating to their age, gender, clinical details, complications rate, and complication types, were collected. The statistical package used for data analysis is Statistics Version 20 (IBM, USA). Data were presented in tables. Results: 120 patients were recruited for the study, 63 males and 57 females; giving male: female ratio of 1.05:1. The mean age range was 54 (18.0) years. Complications were observed in 45 patients (the complication rate was 37.5%). Pleural effusion 27/45 (60%) were the most common complications observed, ARDS and Respiratory failure 9/45 (20%) were second common complications observed, Hypotension and hemodynamic changes 5/45 (11.1%) complications were also seen, Lung abscess 3/45 (6.6%) and Empyema 1/45 (2.3%) were less common complications. Conclusion: Complications rate in patients with CAP though higher in older adult patients then Youngers adults. More common occurring complications are Para Pneumonic Pleural Effusion, ARDS and Respiratory Failure.